Regional Pro Bon Conference Held at Hilton Hotel - Watkins, Howard::::::::: (1989)
State Bar Board of Governors Representatives Robert Oliver (5th District) and Glee Ewell (Public Member) presenting Donald Fischbach State Bar's President's Pro Bono Attorney of the Year Award